Relationship between swimming speed and physiological and perceptual responses in skins race - Tsukahara, Y.; Ueda, T. (Scientific Journal of Sport and Performance, 2023)
Purpose: This study investigated the relationships between swimming speed and physiological and perceptual responses in a skins race, in which a maximum of three races are repeated with a rest in between each round. Methods: The study measured the physiological responses in terms of the heart rate, maximal oxygen uptake (VO2max), and oxygen debt (O2 debt) and examined the perceived exertion to determine the perceptual response. Specifically, it measured the swimming speed and blood lactate (Bla) levels of seven male collegiate swimmers in three rounds of 50 m freestyle, which simulated skins race. It also conducted a bicycle ergometer test to measure their VO2max and O2 debt. Results: The results showed a significant association between swimming speed and Bla. In other words, the study found a significant association between swimming speed and glycolysis during the skins race. However, it did not find a significant association between swimming speed and VO2max or/and O2 debt. Conclusion: Hence, it concluded that a swimmer`s skill level is related to the swimmer`s speed in the skins race. These findings provide an understanding of the physiological parameters that effect performance in high-intensity sports.